Biomechanical analysis of anterior pelvic ring fractures with intact peripelvic soft tissues: a cadaveric study. - Fensky, Florian; Weiser, Lukas; Sellenschloh, Kay; Vollmer, Matthias; Hartel, Maximilian Johannes; Morlock, Michael Maria; Püschel, Klaus; Rueger, Johannes Maria; Lehmann, Wolfgang (European Journal of Trauma & Emergency Surgery, 2021)
Purpose: Biomechanical studies of the pelvis are usually performed using dissected pelvic specimens or synthetic bones. Thereby the stabilising effect of the surrounding soft tissues is analysed insufficiently. Biomechanical data for isolated anterior pelvic ring fractures are currently missing. Therefore, the purpose of this study was to develop a novel testing device for biomechanical analyses of the pelvis and to investigate two different anterior pelvic ring fractures in a cadaveric model with intact peripelvic soft tissues. Methods: A new biomechanical table construction which enables the fixation and testing of complete cadaveric specimens was developed. It was used to investigate the relative motion and stiffness changes due to unilateral osteotomy of the superior and inferior pubic ramus. Five cadavers with a mean age of 55.6 years (± 15.53 years) were included and loaded with a sinusoidal, cyclic (1 Hz), compressive force of up to 365 N over ten cycles for each condition. Results: Biomechanical testing of the pelvis with complete appended soft tissues was feasible. Native stiffness without a pelvic fracture was 64.31 N/mm (± 8.33 N/mm). A standardised unilateral osteotomy of the superior pubic ramus reduced the stiffness under isolated axial load by 2% (63.05 N/mm ± 7.45 N/mm, p = 0.690). Additional osteotomy of the inferior pubic ramus caused a further, statistically not significant, decrease by 5% (59.57 N/mm ± 6.84 N/mm, p = 0.310). Conclusions: The developed test device was successfully used for biomechanical analyses of the pelvis with intact peripelvic soft tissues. In a first study, isolated unilateral fractures of the anterior pelvic ring showed no relevant biomechanical variation compared to the intact situation under isolated axial load. Only 7% of the measured stiffness was created by both unilateral pubic rami. Therefore, the clinical practice to treat unilateral anterior pelvic ring fractures conservatively is supported by the results of this study.